The effect of administration of intravenous intralipid on pregnancy outcomes in women with implantation failure after IVF/ICSI with non-donor oocytes: A randomised controlled trial. (September 2019) - Singh, Neeta; Davis, Amenda Ann; Kumar, Sunesh; Kriplani, Alka
Abstract: Objective: Does the administration of intravenous intralipid in women with previous implantation failure at the time of embryo transfer improve pregnancy outcomes in terms of biochemical pregnancy rate, clinical pregnancy rate, ongoing pregnancy rate, and ongoing pregnancy rate? Study Design: This was a single blinded randomised controlled trial of 105 subjects with previous failed IVF undergoing self donor oocyte IVF/ICSI from January 2017 to May 2018. Randomisation was by computer generated sequence after oocyte pickup. Results were analysed for 102 women, excluding three women due to poor embryo quality. Women in the study arm(n = 52) received 2 doses of 20% intravenous intralipid (Fresenius Kabi), 4 ml diluted in 250 ml normal saline by slow infusion. The first dose was given immediately after oocyte recovery, and the second dose was given on the day of embryo transfer, 1 h prior to the transfer. The control group (n = 50) received normal saline. Flexible ovarian stimulation protocols were used. All the women received routine luteal phase support with micronised vaginal progesterone. Results: 102 women underwent analysis, 52 in the study group and 50 in control group. There was no significant difference in the baseline characteristics. There was a significant difference in the biochemical pregnancy rate in the intralipid group (40.38%) versus control (16%) [(p = 0.006), RR = 2.5 (1.23–5.16 CI)], clinical pregnancy rate [(34.62% vs 14%), p = 0.006, RR = 2.5(1.13–5.40 CI)], implantation rate [(16.6% vs 6.6%), p = 0.012, RR = 2.5(1.18 to 5.41 CI)], and take home baby rate [28.8% vs 10%, p = 0.024, RR = 2.8(1.1–7.3)]. The adjusted odds ratio for clinical pregnancy in women who received intralipid vs placebo was 3.1 (1.02–9.70 95% CI), p = 0.046. No adverse effects of intralipid were observed. Conclusion: This study shows a statistically significant increase in implantation rate and live birth rate in women who receive intravenous intralipid with prior implantation failure after IVF/ICSI. These findings concur with other studies; however, literature is limited. The effect of intralipid on the immunological abnormalities in women who experience recurrent implantation failure needs to be investigated further.